Analisis Kebutuhan Media Detective Game untuk Meningkatkan Minat Belajar Sejarah pada Materi Kedatangan Bangsa Barat ke Nusantara untuk SMA Kelas XI - Rosandy, Willia Dara; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
This research is motivated by the low interest and learning outcomes of high school students in history, as indicated by passive participation and monotonous learning media. These conditions require the development of innovative learning media that are interactive, engaging, and aligned with students’ characteristics. The purpose of this study is to analyze the needs for developing the Detective Game as a history learning medium on the topic of the arrival of Western nations to the Nusantara, as well as to examine its potential effectiveness in supporting classroom learning. This study employed a descriptive qualitative approach with data collection techniques consisting of classroom observation, teacher and student interviews, and questionnaires. The findings show that teachers require more varied and interactive media, students have access to personal devices to support digital media use, and schools provide adequate facilities. In conclusion, the Detective Game has the potential to become an innovative, interactive, and enjoyable history learning medium, capable of enhancing students’ motivation and understanding of history, particularly regarding the arrival of Western nations to the Nusantara.